2005
DOI: 10.1038/sj.eye.6701949
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of central visual function by microperimetry and autofluorescence in patients with Best's vitelliform dystrophy

Abstract: Purpose To evaluate retinal sensitivity and fixation patterns in patients with Best's dystrophy by microperimetry (MP) and to correlate the results with static perimetry and retinal morphology seen by autofluorescence (AF). Methods Central 101 visual fields in 11 patients with Best's dystrophy (VA: 0.570.38) were recorded by the Octopus M2 TOP program and by MP (MP1, Nidek Technologies). AF was recorded by HRA (Heidelberg Engineering). Results High correlation (R ¼ 0.75, À0.76, À0.48) was found between static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…PRL was never situated inside the central uniform hypofluorescent area, but corresponded with the hyperfluorescent ring seen by the autofluorescence imaging [28]. Progression of BVD, indicated with deterioration of VA and more dense central scotomas were detected with static perimetry, which showed a high correlation with MP results [28].…”
Section: Ophthalmological Evaluationmentioning
confidence: 50%
See 4 more Smart Citations
“…PRL was never situated inside the central uniform hypofluorescent area, but corresponded with the hyperfluorescent ring seen by the autofluorescence imaging [28]. Progression of BVD, indicated with deterioration of VA and more dense central scotomas were detected with static perimetry, which showed a high correlation with MP results [28].…”
Section: Ophthalmological Evaluationmentioning
confidence: 50%
“…High correlation (R=0.75, -0.76, -0.48) was found between static perimetry (MS, MD and CLV indices) and MP [28]. Results showed that microperimetry enabled a highly sensitive topographic monitoring of retinal function, showing central or pericentral fixation in the early stages, until loss of central function, in the eyes with visual acuity 0.2 or less has caused evident shift of fixation to preferential retinal locus (PRL) [28]. PRL was never situated inside the central uniform hypofluorescent area, but corresponded with the hyperfluorescent ring seen by the autofluorescence imaging [28].…”
Section: Ophthalmological Evaluationmentioning
confidence: 86%
See 3 more Smart Citations